Disparities in the quality of HIV care when using US Department of Health and Human Services Indicators. - Althoff, Keri N; Rebeiro, Peter; Brooks, John T; Buchacz, Kate; Gebo, Kelly; Martin, Jeffrey; Hogg, Robert; Thorne, Jennifer E; Klein, Marina; Gill, M John; Sterling, Timothy R; Yehia, Baligh; et al. (Clinical infectious diseases : an official publication of the Infectious Diseases Society of America, 2014)
We estimated US Department of Health and Human Services (DHHS)-approved HIV indicators. Among patients, 71% were retained in care, 82% were prescribed treatment, and 78% had HIV RNA ≤200 copies/mL; younger adults, women, blacks, and injection drug users had poorer outcomes. Interventions are needed to reduce retention- and treatment-related disparities.